The convergent validity of the childhood trauma questionnaire (short-form) and the brief betrayal trauma survey in a first-episode psychosis sample - Julie Perrine Schaug; Ole Jakob Storebø; Stephen Fitzgerald Austin; Anne Marie Trauelsen; Marlene Buch Pedersen; Ulrik Helt Haahr; Erik Simonsen (Psychiatry Research Communications, 2023)
Different forms of childhood maltreatment are known to be significant risk factors for psychosis. However, the strength of this relationship is frequently contested due to different findings between studies, partly because of variations in the conceptualizations and assessments of childhood trauma. The objective of the current study was to explore the convergent validity of two childhood trauma instruments, the Brief Betrayal Trauma Survey (BBTS) and the Childhood Trauma Questionnaire short-form (CTQ-SF), in a sample of first-episode psychosis (FEP) participants. This was a cross-sectional study where participants from a Danish early psychosis service (OPUS) were recruited over a 2-year period. Ninety-nine participants were assessed with both instruments, and reports of childhood emotional, physical, and sexual abuse were compared. There were significantly differing reports of childhood trauma in all domains, with higher reports of childhood abuse in the CTQ than in the BBTS. Findings suggest previous heterogeneous results in studies exploring the association between childhood trauma and psychosis could partly be due to different assessments of trauma. Future studies wishing to explore this association should aim to use a common conceptualization of childhood trauma in their assessments.